Promoting Aspirin Use for Cardiovascular Disease Prevention Among an Adult Internet-Using Population: A Pilot Study - Oldenburg, Niki C.; Horvath, Keith J.; Van't Hof, Jeremy; Misialek, Jeffrey R.; Hirsch, Alan T. (Frontiers in Public Health, 2021)
Cardiovascular disease prevention strategies include aspirin use as a preventive measure. The internet can be used to raise public awareness, promote healthy lifestyles, and improve disease management. This pilot study describes the feasibility of an educational website to recruit and follow adult internet users to examine whether they talked to their physician about aspirin and initiated aspirin use. As part of a statewide intervention promoting an aspirin regimen to prevent heart attacks and strokes in Minnesota, visitors to the website were encouraged to complete an aspirin candidacy tool. Between October, 2015 and February, 2016, men 45-79 and women 55-79 who identified as aspirin candidates were invited to participate in a 6-month study involving four, 5-minute online surveys to examine physician discussions about aspirin, aspirin use, and mobile technology use. During the 5-month recruitment period, 234 adults enrolled in the study. Of the 174 who completed the baseline survey and at least one follow-up survey, 74 (43.5%) did not use aspirin at baseline. During follow-up, 12 (16.2%) talked to their doctor about aspirin and 31 (41.8%) initiated aspirin use. Internet, social media, and mobile technology use were high among this population. An educational website may have provided a cue to action for aspirin discussions with physicians and aspirin initiation. More research is needed to evaluate the utility of on-line tools to increase appropriate aspirin use among internet-using populations.